2016
DOI: 10.1186/s13104-016-2088-1
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological quality of raw camel milk along the market value chain in Fafen zone, Ethiopian Somali regional state

Abstract: BackgroundThe camel is a multipurpose animal with a huge productive potential. Camel milk is a key food in arid and semi-arid areas of the African and Asian countries. The quality of milk is influenced by different bacteria present in milk. This study was conducted to evaluate total bacterial content in raw camel milk along the market chain in Fafen zone, Ethiopian Somali Regional State.MethodsOne hundred twenty-six raw camel milk samples were collected from Gursum (47.1 %) and Babile (52.9 %) districts. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 7 publications
2
40
1
Order By: Relevance
“…We undertook a standard plate count of aerobic bacteria using the pour plate method (Abera et al, 2016) and expressing the count in colony-forming units per milliliter (cfu/mL). Camel and bovine milk contained 2.9 and 3.1 log 10 cfu/mL, respectively.…”
Section: Microflora Counts In Camel and Bovine Milkmentioning
confidence: 99%
“…We undertook a standard plate count of aerobic bacteria using the pour plate method (Abera et al, 2016) and expressing the count in colony-forming units per milliliter (cfu/mL). Camel and bovine milk contained 2.9 and 3.1 log 10 cfu/mL, respectively.…”
Section: Microflora Counts In Camel and Bovine Milkmentioning
confidence: 99%
“…However, with the exception of one or two reports from the region to the best of our knowledge, detailed studies on the microorganisms associated with camel milk are almost missing especially from Saudi Arabia. This study aimed at identifying the culturable microbial community associated with camel milk using molecular approaches.…”
Section: Discussionmentioning
confidence: 95%
“…As far as camel milk from Saudi Arabia is concerned, not many detailed studies on the milk‐associated bacteria are available. Few studies have reported colony‐forming units, lactic acid bacteria, or coliforms in camel milk using conventional methods . Very few studies on the PCR‐based detection of the pathogens such as Brucella in camel milk are also available .…”
mentioning
confidence: 99%
“…The environment is a contributing factor to cross-contamination of Suusac. Milking area is usually open and dusty hence possibility of contaminating the milk and milk containers with microorganisms from the soil, milking personnel or camel coat during milking [35,36]. The study was done in the months of July and August when it was extremely dry and dusty hence high levels of contamination from the dust.…”
Section: Discussionmentioning
confidence: 99%